Technology acceptance of mobile health applications in GCC countries: case of Kuwait - Banna, Sumayya; Ottesen, Andri (International Journal of Engineering and Technology, 2019)
Information technologies solutions have proven to bring many opportunities. For instance, the information technologies have proven to improve the efficiency and effectiveness of healthcare in the developed countries. However, the drivers and barriers to accept mobile applications and information technologies adoption within healthcare are little researched for the GCC countries where the information technologies adoption is relatively new. The current research is a pilot study that investigate unbiased evaluation of different end-usersâ€™ views on information technologies solutions in Kuwait. To catch up with the growth, the GCC countries have attempted to revolutionize the healthcare systems throughout the applications of information technologies solutions including mobile computing solutions and educate users with better methods to receive customized health services. The present paper examined the issues by using the framework of Technology Acceptance Model (TAM) and Q methodology to grasp insights and reflections of different viewpoints of end-userâ€™s adoption factors. One of the findings indicated that the perceived security risk was the least an obstacle factor for mobile applications adoptions and acceptance. Another chief factor for such adoption is the perceived usefulness and perceived ease of use domains which present significant elements for the escalating embracing of mobile health application among end-users in Kuwait. Accordingly, the data analytics indicated two factors labeled as â€œtechnology readinessâ€ competent end-users and â€œrisk insensitiveâ€ end-users.Â
Keywords: Information Technology; Kuwait; Q Method; Technology Acceptance Mode (TAM); Mobile Health applications.